Creative Strategies in Music Composition Learning : A Literature Review on Stimulating Student Creativity - Puri, Tia Destiana; Hutapea, Clarisa Jesika Korina Tiurmauli; Aprianti, Yanti Nur; Milyartini, Rita (Jurnal Paedagogy, 2025)
This study aims to explore various creative strategies that music educators can use to stimulate students' creativity, so that they can produce original and meaningful musical works. The research method used is a literature review of various pedagogical approaches in learning music composition. The sources of research data come from various journal articles, books, and scientific publications relevant to the topic of music composition learning strategies and student creativity development. The data analysis technique was conducted through content analysis of the reviewed literature to identify learning strategies that are effective in fostering students' creative thinking, musical exploration, and artistic expression. The research findings show that learning music composition is an important aspect of music education because it can develop students' creativity as a whole, especially at the primary and secondary education levels. Approaches such as Experiencing Composition as well as the support of the learning environment, the active role of teachers, and the utilization of technology are important factors in creating learning experiences that encourage students to create authentic and meaningful musical works.